A influência da estrutura de paisagens agrícolas nos índices de diversidade de aves - Matos, Veridiana Possati Vieira de (2015)
Habitat loss and fragmentation are currently the main causes of the global extinctions, caused mostly by replacing of the native vegetation by different land-uses. The graph theory supports the understanding of the landscapes, considering the permeability of land-uses/land-covers. The objective of this study was to evaluate the influence of the landscape spatial patterns, in this case National Forest (FLONA) of Capão Bonito and buffer zone, in the bird diversity. We defined 80 collection points in the four levels of forest connectivity, previously defined in the landscape, which were visited five times. The “fix point” method was used for species detection, with 10 minutes for sampled time. We calculated Shannon Wiener diversity index (H '), Abundance Index values (IPA), richness in order to evaluate changes in the bird community, besides the classification of species by trophic categories. The land-uses/landcover were grouped into MNA (Forest); FP (pine, araucaria and eucalyptus) and AGRP (agriculture and pasture). We evaluated the similarity among this groups, considering the IPA and species numbers, through non-metric multidimensional scaling graphics (NMDS). According the analysis there was similarity between MNA and FP, which are heterogeneous, increasing the stability for birds at the landscape scale. Although, the dissimilarity obtained for AGRIP is consequence of the land-use be a homogeneous environment, with less diversity of resources. The evaluation of the matrix permeability was analyzed from the perspective of graph theory, using the Connectivity Integral Index (IIC), redundancy analysis (RDA) of NMDS and multiple regression. The IIC was generated for two situations: with the impedance values (IICc) and without (ICCe). We defined the follow resistance values: 30% for agriculture and 60% for pasture. The permeability analysis indicated agriculture as land-use with the most influence in the bird community variance. So, we concluded that the less complex sites has the less diversity and species richness than the sites more complexes.